Gender and race in neurotrauma: part 1-identifying inequalities in leadership, academics, and clinical trial management - Churchill, Isabella F.; Sue, Téa; Parr, Ann M.; Tsai, Eve C. (Frontiers in Neurology, 2024)
Gender and racial equality, or the lack thereof, is a constantly recurring theme in neurosurgery and under-reported in neurotrauma literature. This perspective piece addresses the underrepresentation and challenges faced by women and racial minorities in neurosurgery, and within the workforce of neurotrauma, specifically. The literature demonstrates that there is still a scarcity of females and racial minorities in neurosurgery leadership positions and that females are less likely to receive invited papers. The persistent challenges in navigating gender and racial dynamics in neurosurgery/neurotrauma underscore the need for progress in advancing intersectionality within the field, emphasizing the importance of addressing inequalities. Several strategies to improve gender and racial diversity in neurotrauma workforce, leadership and academics are presented.